The fundus in height - Haro, Daniel Enrique (1966)
The author studies the characteristics of the fundus in 50 subjects acclimatized to 4,540 m. above sea level, having finding notorious ophthalmoscopic changes. The fundus changes that give the peculiar characteristic in men acclimatized to high altitudes are mainly of vascular origin: papillary hyperemia, vascular dilation and tortuosity, venous engorgement large, shiny dark hyperemic retina, macula with discoid, dark appearance and with increased reflexes and great perimacular vascularization. These changes are due to the constant climate hypoxic condition in which they live and are made based on the increased oxygenation capacity and surface diffusion from the blood to improve the nutrition of the retina; hemctolócrícos intervening factors such as hyper - volernio, polycythemia and increased Hb level, reduced and vasodilation, as demonstrated in other organs. The great variability of fundus changes makes it difficult to determine the time required for its appearance in subjects ascending plain, and its reversibility in those who descend and remain d31 sea level, has not been tested.